TRANSPLANTASI HUKUM MODERN TERHADAP BUDAYA HUKUM KOMUNITAS PENGRAJIN DALAM MELINDUNGI DESAIN TRADISIONAL KERAJINAN PERAK CELUK DI KABUPATEN GIANYAR BALI - Simona Bustani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2016)
Currently, traditional design violations often occur that impact on economic losses. This remained the case even though Indonesia has a law design. One problem is the lack of effective implementation of the law in protecting traditional designs Celuk Silver. Therefore, how the impact of the law against legal culture transplant community craftsmen silver in Celuk Gianyar Bali in protecting traditional design in the era of globalization? How efforts to improve the legal culture community silversmith in Celuk Gianyar Bali in protecting traditional design motif in the era of globalization? For that type of normative legal research used socio-legal approach, the nature of descriptive research. Analyzed qualitatively. Law transplanted modern laws that have an impact on culture clash the laws of society that is sketched on the level of public knowledge silversmith about a law design only 20 %, while the related understanding silversmith about the content of the regulation 10%, while revenues silversmith against a law design only 8 %, and community artisans who did not know about a law design is 45 %, the remaining 17 % abstained. Therefore, efforts need to be done is to from a team to the youth Bali socializing, exploring, involving institutional organizations associated Balinese silversmiths in Bali to collect data and to receive input on drafting regulations that support protection of traditional craft design motif. However, the role of local government and communities had not been sufficient to achieve maximum results. Therefore, maximum effort is needed in doing the role of the central government in providing facilities and infrastructure for data collection by involving community organizations and local government silversmith preparing the legislation relating to the protection of traditional design motif silver Celuk Bali representing regional assets.